Construct Validity of the Knowledge and Skills in a Geography STEM Education Instrument among Prospective Teachers: Confirmatory Factor Analysis - Mahat Hanifah; Sumayyah Aimi Mohd Najib; Saiyidatina Balkhis Norkhaidi; Nurul Hidayah Baharuddin (Faculty of Geography, Universitas Gadjah Mada, 2021)
Science, Technology, Engineering, and Mathematics (STEM) subjects refer to school education policies and curriculum options to increase competitiveness in science and technology for students. Geography connects STEM disciplines with the application of geographical technology and tools, which can better understand cross-disciplinary phenomena to address critical problems. This study was carried out to validate the construct of the knowledge and skills in a geography STEM education instrument among prospective teachers in Malaysia. The respondents consisted of 400 students of semesters one to eight from the Bachelor of Education in Geography program, Universiti Pendidikan Sultan Idris, Perak, Malaysia, who were selected using a simple random sampling technique. The constructs studied were the knowledge and skills in geography STEM education. The data were analyzed descriptively and inferentially using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) for item component grouping. The analysis results showed that the reliability value of Cronbach's alpha was at a high classification, which exceeded 0.70. The result of the EFA showed two components generated from the knowledge construct: STEM Knowledge and Applied Knowledge, and one component from the skill construct known as STEM Skill. Regarding the measurement model, CFA results showed that the solution was suitable and acceptable based on the suggested indicators. Therefore, the 25-item measurement model developed is suitable to measure the knowledge and skills in geography STEM education among prospective teachers in Malaysia.